Sodium and potassium urinary excretion and dietary intake: A cross-sectional analysis in adolescents - Gonçalves, Carla (2016)
Background: Hypertension is the leading cause for heart disease and stroke, for mortality and morbidity worldwide, and a high sodium-to-potassium intake ratio is considered a stronger risk factor for hypertensionthan sodium alone.Objective: This study aims to evaluate sodium and potassium urinary excretion, and assess the food sourcesof these nutrients in a sample of Portuguese adolescents.Design: A cross-sectional study with a sample of 250 Portuguese adolescents. Sodium and potassium excretion were measured by one 24-h urinary collection, and the coefficient of creatinine was used to validate completeness of urine collections. Dietary sources of sodium and potassium were assessed using a 24-h dietary recall.Results: Valid urine collections were provided by 200 adolescents (118 girls) with a median age of 14.0 in bothsexes (p0.295). Regarding sodium, the mean urinary excretion was 3,725 mg/day in boys and 3,062 mg/dayin girls (pB0.01), and 9.8% of boys and 22% of girls met the World Health Organization (WHO) recommendations for sodium intake. Concerning potassium, the mean urinary excretion was 2,237 mg/day inboys and 1,904 mg/day in girls (pB0.01), and 6.1% of boys and 1.7% of girls met theWHOrecommendations for potassium intake. Major dietary sources for sodium intake were cereal and cereal products (41%), meat products (16%), and milk and milk products (11%); and for potassium intake, main sources were milk and milk products (21%), meat products (17%), and vegetables (15%).Conclusions: Adolescents had a high-sodium and low-potassium diet, well above the WHO recommendations.Health promotion interventions are needed in order to decrease sodium and increase potassium intake.